Topicalization and Anaphor in Mongolian - V.Dashdavaa (Acta Mongolica, 2015)
Mongolian reflexive uuruu (self) seems to violate from the Principle of Binding Theory on the scope of Government and Binding work and Minimalist program. Since it is considered to be reflexive they are predicted to conform to Government & Binding principles.